Rekayasa, Takhta dan Malapetaka: Sebuah Pedoman - Kuswantoro; Masduki Asbari (Yayasan Aya Sophia Indonesia, 2022)
The purpose of this research is to find out Gita Wirjawan's views from Gita Wirjawan's youtube channel entitled